Hippocampal Astrocytes in Migrating and Wintering Semipalmated Sandpiper Calidris pusilla - Carvalho-Paulo, Dario; de Morais Magalhães, Nara G.; de Almeida Miranda, Diego; Diniz, Daniel G.; Henrique, Ediely P.; Moraes, Isis A. M.; Pereira, Patrick D. C.; de Melo, Mauro A. D.; de Lima, Camila M.; de Oliveira, Marcus A.; Guerreiro-Diniz, Cristovam; Sherry, David F.; et al. (Frontiers in Neuroanatomy, 2018)
Seasonal migratory birds return to the same breeding and wintering grounds year after year, and migratory long-distance shorebirds are good examples of this. These tasks require learning and long-term spatial memory abilities that are integrated into a navigational system for repeatedly locating breeding, wintering, and stopover sites. Previous investigations focused on the neurobiological basis of hippocampal plasticity and numerical estimates of hippocampal neurogenesis in birds but only a few studies investigated potential contributions of glial cells to hippocampal-dependent tasks related to migration. Here we hypothesized that the astrocytes of migrating and wintering birds may exhibit significant morphological and numerical differences connected to the long-distance flight. We used as a model the semipalmated sandpiper Calidris pusilla, that migrates from northern Canada and Alaska to South America. Before the transatlantic non-stop long-distance component of their flight, the birds make a stopover at the Bay of Fundy in Canada. To test our hypothesis, we estimated total numbers and compared the three-dimensional (3-D) morphological features of adult C. pusilla astrocytes captured in the Bay of Fundy (n = 249 cells) with those from birds captured in the coastal region of Bragança, Brazil, during the wintering period (n = 250 cells). Optical fractionator was used to estimate the number of astrocytes and for 3-D reconstructions we used hierarchical cluster analysis. Both morphological phenotypes showed reduced morphological complexity after the long-distance non-stop flight, but the reduction in complexity was much greater in Type I than in Type II astrocytes. Coherently, we also found a significant reduction in the total number of astrocytes after the transatlantic flight. Taken together these findings suggest that the long-distance non-stop flight altered significantly the astrocytes population and that morphologically distinct astrocytes may play different physiological roles during migration.